Finite element analyses on a small masonry house prototype retrofitted using frp strips - Ahmad Basshofi Habieb; Marco Valente; Gabriele Milani (Journal of Civil Engineering, 2020)
This study presents a series of finite element analyses on the prototype of masonry house retrofitted using FRP strips.The model of the masonry house refers to the prototype scaled to 1:3 tested in an experimental campaign. The non-linear behaviorof masonry is modeled through the Concrete Damage Plasticity (CDP) model, while the FRP and adhesive are modeled as twoseparated isotropic solid materials with elastic-plastic behavior. A good agreement between experimental and numerical resultis obtained, indicating the increase of bearing capacity of the reinforced masonry prototype.